EDUCATION FOR THE DIGITAL GENERATION: TEACHING WITH THE HELP OF INTERACTIVE TECHNOLOGIES (Innovate Conferences, 2025)
This article highlights the advantages and problems of teaching representatives of the digital generation using interactive technologies in modern education. It is emphasized that the use of digital tools serves to develop students' motivation, independent thinking, and creative approach. It also analyzes the didactic and psychological foundations of the technological approach, along with practical experiences.